Prevalence and factors associated with childhood visual impairment in Ethiopia - Bezabih L (Dove Medical Press, 2017)
Lidiya Bezabih,1 Tilaye Workneh Abebe,1 Robera Olana Fite2 1Department of Public Health, College of Health Sciences, Adama General Hospital and Medical College, Adama, 2Department of Nursing, College of Medicine and Health Sciences, Wolaita Sodo University, Wolaita Sodo, Ethiopia Background: Visual impairment is a significant loss of vision. It has an impact on the prosperity of different countries. It has been difficult to plan preventive measures against visual impairment due to the scarcity of data about the extent of the problem.Objectives: The study was aimed at assessing the prevalence and identifying factors associated with visual impairment among school-age children in Ethiopia.Materials and methods: A cross-sectional study design was used in four randomly selected schools found in Addis Ababa from May 15 to June 14, 2016. A total of 804 school-age students were selected using the simple random sampling method. Bivariable logistic regression and multivariable logistic regression were conducted. A p-value <0.05 was taken as a significant association.Results: A total of 718 students participated in the study, obtaining a response rate of 89.3%. In all, 7.24% of school-age children were visually impaired, of whom 3.9% had low vision and 3.34% had severe visual impairment. Factors associated with visual impairment were being female (adjusted odds ratio [AOR], 2.28; 95% confidence interval [CI], 1.06–3.50), being in the age group of 10–13 years (AOR, 2.94; 95% CI, 1.36–6.22), being in the age group of 14–18 years (AOR, 4.06; 95% CI, 2.17–11.95), being a private school student (AOR, 2.61; 95% CI, 1.81–4.41), watching television for 2–4 hours/day (AOR, 3.56; 95% CI, 1.37–7.34), watching television at <1 m (AOR, 7.65; 95% CI, 2.59–34.61), watching television at 1–2 m (AOR, 6.89; 95% CI, 1.74–25.27), mobile exposure for 2–4 hours/day (AOR, 2.61; 95% CI, 1.35–4.58), mobile exposure for >4 hours/day (AOR, 3.05; 95% CI, 1.41–9.18), medical visit while experiencing symptoms (AOR, 11.32; 95% CI, 1.80–82.25) and no medical visit experience (AOR, 3.84; 95% CI, 0.46–31.76).Conclusion: The majority of the visually impaired school-age children had low vision. Sex, age, school type, television exposure duration, the distance of television exposure, mobile exposure and medical visit were factors associated with visual impairment. Increasing community awareness about early detection of visual impairment and providing affordable eye health service may decrease the prevalence of visual impairment. Keywords: Adama, visual impairment, children, amblyopia